Perhitungan harga pokok produksi berdasarkan metode Full Costing untuk penetapan harag jual produk pada CV. Silvi MN Paradilla Parengan - Laras Sukma Arum Melati; Guntur Saputra; Faridatun Najiyah; Fitria Asas (Politeknik Ganesha Medan, 2022)
The problem that becomes the background of this research is in determining the selling price of a basic product that is used is the calculation of the cost of production, which is a way to take into account the determination of cost elements into the cost of the product and the selling price that is set must be able to determine all costs that produce long term profit. Based on the determination of the correct product cost of a product, it will be able to reduce uncertainty in determining the selling price. The purpose of this study is to find out how to calculate the cost of production based on the full costing method for determining the selling price of the product. In determining the selling price of the product, the selling price method is used based on cost-plus pricing. Cost plus pricing is the determination of the price by adding a certain amount (percentage) of the selling price or cost as profit. The method used in this study is quantitative descriptive analysis method, the results of this study indicate that there are advantages in calculating the cost of goods manufactured based on the Full Costing method and to be able to determine the cost of goods sold, the production costs must be calculated at the beginning of each month based on the previous period's sales report.